Empathic responses are reduced to competitive but not non-competitive outgroups - Richins, M. (2019)
Individuals feel more empathy for those in their group (i.e. ingroup members) than those who are not (i.e. outgroup members). But empathy is not merely selective to group distinctions, rather it fluctuates according to how groups are perceived. The goal of this research was to determine whether group-based evaluations can drive biases in self-reported empathy as well as in the underlying neural activity. Participants were asked to rate a target's physical pain while BOLD responses were recorded via functional magnetic resonance imaging (fMRI). The target was either a member of the ingroup or one of two outgroups, one which was more of a rival to the ingroup than the other. Participants reported feeling more empathy for targets experiencing painful compared to innocuous events, showing bias only in favour of their ingroup. Neural responses were stronger while observing painful, compared to innocuous, events but only for targets from the ingroup or the less competitive outgroup. The difference was non-significant and trended in the opposite direction when the target was from the more competitive outgroup. This provides evidence that empathy is not merely selective to "us" vs "them" but is more nuanced by whom we refer to by "them".